Liikunta stressinhallinnan välineenä. Eri liikuntamuotojen ja niiden ominaisuuksien yhteys koettuun stressiin - Niemi, Satu; Liljenmaa, Klaudia (2025)
Liljenmaa, K. & Niemi, S. 2025. Exercise as a tool for stress management. The relationship between different types of exercise and their characteristics with perceived stress. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis in Sport Pedagogy, 58 pp., 4 appendices.